Effect of physical activity combined with extra ciliary-muscle training on visual acuity of children aged 10–11 - Yin, Rongbin; Xu, Jianrong; Wang, Hongyun; Zhou, Sheng; Zhang, Meng; Cai, Geng (Frontiers in Public Health, 2022)
This study is intended for exploring the effects of the physical activity combined with extra ciliary-muscle training with different frequencies on children's kinetic visual acuity and uncorrected distance visual acuity, and eventually figuring out the optimal frequency of ciliary-muscle training for each physical education class. To do the present research, A total of 160 students aged 10–11 from a school in Suzhou (a major city located in southeastern Jiangsu Province, East China) were randomly selected and divided into control group (n = 33), 15-frequency group (n = 44), 30-frequency group (n = 40) and 60-frequency group (n = 43), and the latter three experimental groups participated in a specially designed physical activity plan based on the training principles of ciliary muscle, while the control group participated in normal physical activity as usual. The experimental intervention period was 16 weeks, and all students' kinetic visual acuity and uncorrected distance visual acuity were measured before and after the experiment. The result showed that the kinetic visual acuity of the students in the 30 and 60-frequency groups got improved significantly after the experiment (p < 0.05), with the highest improvement occurring in the 30-frequency group, while there was no significant change in the 15-frequency group and the control group; The uncorrected distance visual acuity of the students in the 30 and 60-frequency groups was significantly improved after the experiment (p < 0.05), and the improvement range in these two groups was similar. In contrast, there was no significant change in the 15-frequency group, while the control group showed a significant decrease (p < 0.05). Physical activity combined with extra ciliary-muscle training has a positive effect on improving children's vision; at the same time, ciliary-muscle training with different frequencies bring out different outcomes on children's vision improvement, among which ciliary-muscle training with frequency of 30 in each physical education class is the best choice to enhance children's kinetic visual acuity and uncorrected distance visual acuity.